PHYSICS LEARNING MEDIA USING ADOBE FLASH CS6 TO REMEDIATE STUDENTS' MISCONCEPTIONS ON NEWTON'S LAW MATERIALS - Arif Wiratama (Physics and Science Education Journal (PSEJ), 2022)
This research aims to determine the feasibility of developing, theoretical, practical, and effectiveness of interactive multimedia on Newton's law material. This research was motivated by frequent misconceptions, physics learning difficulties, and students' needs for an interesting instructional media. This development research used the ADDIE model development design. Data collection techniques used questionnaires and multiple-choice questions. Data analysis techniques used in research and development were qualitative and quantitative. Qualitative was used to describe data in the form of comments and suggestions for improvement from validators, teachers, and students. While quantitative was used to process data in the form of scores from research by teachers and students as well as to process the effectiveness test results data. Based on the results of the validation of multimedia development by instructional material and media experts, declared valid and able to be tested, while the results of the teacher's response obtained a percentage of 87.14% in the excellent category, the results of student responses in the one-on-one trial obtained a percentage of 94% in the very good category, the results of student responses in small group trials obtained a percentage of 90.1% in the excellent category, and the results of the effectiveness of students experiencing misconceptions ranged between 12.5% and 37.5% as much as 1 person to 3 students. So it can be concluded that learning outcomes using multimedia can improve student understanding of concepts.